Cultivating anti-corruption moral habits: a philosophical and normative legal analysis - Yudisetyo, Zerry Akbar; Razaq, Muhammad Abdul; Prasetyo, Dossy Iskandar (Law and Economics, 2025)
Corruption in Indonesia has evolved into a systemic crisis that threatens democratic institutions, hinders economic progress, and erodes social justice. This study aims to develop a theoretical framework for cultivating anti-corruption moral habits by integrating philosophical ethics with legal structural reform. Employing a normative legal research methodology, the analysis draws upon classical moral philosophies—Socrates’ reflective accountability, Plato’s model of moral leadership, and Aristotle’s concept of the state as a moral educator—alongside contemporary anti-corruption theories. The study identifies four key pillars necessary for sustainable anti-corruption strategies: systemic certainty in governance, habitual ethical reflection in daily decision-making, moral exemplarity among public leaders, and institutional arrangements that nurture civic virtue. The findings suggest that combating corruption effectively requires not only legal reform but also moral reconstruction across individuals, leadership, and institutions. This integrative approach offers meaningful insights for legal philosophy and public governance reform in Indonesia and similar developing contexts.